Cross-sectional study of association between psychosocial stressors with chronic kidney disease among migrant and non-migrant Ghanaians living in Europe and Ghana: the RODAM study. Issue 8 (1st August 2019) - Adjei, David Nana; Stronks, Karien; Adu, Dwomoa; Beune, Erik; Meeks, Karlijn; Smeeth, Liam; Addo, Juliet; Owusu-Dabo, Ellis; Klipstein-Grobusch, Kerstin; Mockenhaupt, Frank; Schulze, Matthias; Danquah, Ina; et al.
Abstract : Objectives: The association between psychosocial stressors (PS) and chronic kidney disease (CKD) among sub-Saharan African (SSA) populations is unknown. We examined the association between PS and CKD prevalence among rural and urban Ghanaians and Ghanaian migrants living in three European cities. We also assessed if the influence of PS on CKD is partially mediated by primary risk factors (hypertension and diabetes) of CKD. Design: A multi-centred cross sectional data from the Research on Obesity and Diabetes among African Migrants study. Setting: Rural and urban Ghana and three European cities (Amsterdam, Berlin and London). Participants: A random sample of 5659 adults (Europe 3167, rural Ghana 1043 and urban Ghana 1449) aged 25–70 years. Explanatory measures: PS defined by negative life events, perceived discrimination, perceived stress at work/home and depressive symptoms. Three CKD outcomes were considered using the 2012 Kidney Disease: Improving Global Outcomes severity of CKD classification. Comparisons between PS and CKD outcomes were made using logistic regression analyses across all sites. Results: We observed higher proportion of negative life events (68.7%) and perceived permanent stress (15.9%) among Ghanaians living in Ghana than Ghanaians living in Europe. Depressive symptoms (7.5%) and perceived discrimination (29.7%) were more common among Ghanaians living in Europe than Ghanaians living in Ghana. No significant association was observed between any of the PS constructs and CKD outcomes across sites except for positive association between stress at work/home and albuminuria (2.81, 95% CI 1.46 to 5.40) and CKD risk (2.78, 95% CI 1.43 to 5.43) among Ghanaians living in Berlin. Conclusion: Our study found a positive association between stress at work/home and albuminuria and CKD risk. There was no convincing evidence of associations between the other PS constructs and the prevalence of CKD risk. Further studies are needed to identify potential factors driving the high prevalence of CKD among these populations.